Một số nguyên lý hoạt động của kho dữ liệu (Data warehouse) - Thi, Vũ Đức; Khôi, Lê Hải (Journal of Computer Science and Cybernetics, 2016)
Data warehousing is the biggest trend in information management today. It is the technology which may finally deliver on a dream pursued by management theorists since the 1960s. In this paper we present the general definition of data warehouse, differences between data warehouse and database management system and some essential principles of data warehouse